Connective Tissue Mobilization Vs. Combination of Taping with Pelvic Tilt on Primary Dysmenorrhea.: Life Sciences -Physiotherapy - Muthulakshmi, K.; Monesh, D.; Moses, Srilakshmi; Aunselvi, J.; Ebenezer Cyrus, Bernard; Gunasekar, Thirulogachandar; V.S., Rakshana. (International Journal of Life Science and Pharma Research, 2023)
Primary dysmenorrhea is pain aggravation on menstruation without any pelvic disease. It is perhaps the most widely recognizedissue females face, influencing them physically and mentally. Connective tissue mobilization can help venous return by increasing theproduction of prostaglandin and different substances and preventing their collection in the pelvis, which can be powerful during the period,to reduce the pain aggravation and inconvenience. This study examines the effects of connective tissue mobilization vs. a combination oftaping and pelvic tilt on unmarried women with primary dysmenorrhea. This is an experimental design with pre and post-comparativestudy. This was conducted in the physiotherapy outpatient department at ACS Medical College and Hospital. The study duration was about3 months. The subjects aged 18 to 25 years female with primary dysmenorrheal were included in this study. The subject with Pelvicinflammatory disease, Uterine/ovarian tumor, Spinal pathology, deformity, and PCOD, were excluded from this study. 30 subjects wereselected and divided into 2 groups in which Group-A 15 received connective tissue mobilization for 3-4 minutes with a total of 20minutes/day a day before menstruation for 3 days for consecutive 3 months, and Group B received taping with pelvic tilt was given 4 daysfor lower abdomen and lumbar, one day before menstruation taping was applied and pelvic tilt was given 2-3 minutes for 20 minutes/dayfor 3 consecutive months The outcome measures were a pain. The outcome tools were the Menstrual symptom questionnaire, Numericalrating scale, and WaLIDD score. Comparing the pretest and posttest within Group A and Group B, Group B shows a highly significantdifference in Mean values at P <_0.001. Thus this study concludes that a combination of taping and pelvic tilt reduces pain in unmarriedwomen having primary Dysmenorrhea.